Cytopathogenicity of Classical Swine Fever Virus Correlates with Attenuation in the Natural Host - Gallei, Andreas (American Society for Microbiology (ASM), 2008)
For the important livestock pathogens classical swine fever virus (CSFV) and bovine viral diarrhea virus (BVDV), cytopathogenic (cp) and non-cp viruses are distinguished according to the induction of apoptosis in infected tissue culture cells. However, it is currently unknown whether cp CSFV differs from non-cp CSFV with regard to virulence in the acutely infected host. In this study, we generated helper virus-independent CSFV Alfort-Jiv, which encompasses sequences encoding domain Jiv-90 of cellular J-domain protein interacting with viral protein (Jiv). Expanding the knowledge of BVDV, our results suggest that Jiv acts as a regulating cofactor for the nonstructural (NS) protein NS2 autoprotease of CSFV and initiates NS2-3 cleavage in trans. For Alfort-Jiv, the resulting expression of large amounts of NS3 correlated with increased viral RNA synthesis and viral cytopathogenicity. Moreover, both cp Alfort-Jiv and the parental non-cp CSFV strain Alfort-p447 efficiently replicate in cell culture. Animal experiments demonstrated that in contrast to parental non-cp Alfort-p447, infection with cp Alfort-Jiv did not cause disease in pigs but induced high levels of neutralizing antibodies, thus elucidating that cp CSFV is highly attenuated in its natural host. In contrast to virulent Alfort-p447, the attenuated CSFV strain Alfort-Jiv induces the expression of cellular Mx protein in porcine PK-15 cells. Accordingly, the remarkable difference between cp and non-cp CSFV with regard to the ability to cause classical swine fever in pigs correlates with different effects of cp and non-cp CSFV on cellular antiviral defense mechanisms.